Respon glukosa darah ikan Betok (Anabas testudineus) terhadap stres padat tebar - Ricky Djauhari; M Matling; Shinta Sylvia Monalisa; Eria Sianturi (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2019)
This research was conducted with the aim to evaluate the performance of blood glucose of Climbing Gouramy (Anabas testudineus) in response to stocking density stress. Fish weighing an average of 2.21 g with a weight of 27 individuals were given stocking density stress by inserting them into 9 cylindrical containers of 200.96 cm2 width and 3 L volume of peat water with stocking differently for 72 hours. These stocking density treatments are A (2 fishes/0.02 m2), B (3 fishes/0.02 m2) and C (4 fishes/0.02 m2) with three replicates. Blood glucose collected from 1 fish per container at 72 hours. The preliminary test was conducted to determine the oxygen demand of fish through the oxygen consumption level test which can then be calculated oxygen demand from the fish in accordance with the density used. The average value of blood glucose levels of Climbing Gouramy that were given the stress of stocking density 2 fishes / 0.02 m2, 3 fishes / 0.02 m2 and 4 fishes / 0.02 m2 tends to be low, that is 53 mg / dL, 52.67 mg / dL and 49.33 mg / dL respectively. The response of blood glucose to stocking density stress results in stocking recommendations for culture Climbing Gouramy ranging from 100-200 fish / m2. Keywords : Blood glucose, Climbing Gouramy, Anabas testudineus, stress, stocking density